Evaluation of Apparent Metabolizable Energy and Apparent Ileal Amino Acid Digestibility of Spirulina (Arthrospira platensis) in Broiler Chickens and Laying Hens - Taylor K. O’Lear Reid; Katherine E. Gardner; Kayla L. Paglia; Alexandra C. M. Ulans; Ruth E. Spierling; Mark S. Edwards; Tryg J. Lundquist; Zach D. McFarlane; Siroj Pokharel; Darin C. Bennett (Animals)
Our study objective was to determine the apparent metabolizable energy (AME) and apparent ileal amino acid digestibility (AIAAD) of spirulina fed to broiler chickens and laying hens using the difference method. In both experiments, birds were either fed corn-soybean meal basal diets, containing no spirulina and formulated to provide the nutrient requirements of either broilers or layers, or fed test diets consisting of 25% spirulina and 75% of the appropriate basal diet. Titanium dioxide was added to all diets as an indigestible marker. The diets were fed to 10 replicate cages/treatment of broilers and 15 replicate cages/treatment of laying hens. The AME of spirulina for broilers was significantly lower (p < 0.05) (2368 ± 104 kcal/kg, as fed) than for laying hens (3144 ± 173 kcal/kg, as fed), suggesting bird type and age may influence energy utilization. The AIAAD of spirulina fed to broiler chickens did not differ from that of laying hens (p > 0.05), except for valine, alanine, and glycine, which were all significantly higher in laying hens (p < 0.05). Overall, the AIAAD for nonessential amino acids averaged 81.1%, with no significant difference between essential and nonessential amino acids. Differences in spirulina nutrient content cited in the literature support further research to determine the optimal inclusion of this alternative ingredient in broiler and layer diets.